Visual exploration and analysis of ionospheric scintillation monitoring data: The ISMR Query Tool - Vani, Bruno César [UNESP] (2017)
Ionospheric Scintillations are rapid variations on the phase and/or amplitude of a radio signal as it passes through ionospheric plasma irregularities. The ionosphere is a specific layer of the Earth's atmosphere located approximately between 50 km and 1000 km above the Earth's surface. As Global Navigation Satellite Systems (GNSS) – such as GPS, Galileo, BDS and GLONASS – use radio signals, these variations degrade their positioning service quality. Due to its location, Brazil is one of the places most affected by scintillation in the world. For that reason, ionosphere monitoring stations have been deployed over Brazilian territory since 2011 through cooperative projects between several institutions in Europe and Brazil. Such monitoring stations compose a network that generates a large amount of monitoring data everyday. GNSS receivers deployed at these stations – named Ionospheric Scintillation Monitor Receivers (ISMR) – provide scintillation indices and related signal metrics for available satellites dedicated to satellite-based navigation and positioning services. With this monitoring infrastructure, more than ten million observation values are generated and stored every day. Extracting the relevant information from this huge amount of data was a hard process and required the expertise of computer and geoscience scientists. This paper describes the concepts, design and aspects related to the implementation of the software that has been supporting research on ISMR data – the so-called ISMR Query Tool. Usability and other aspects are also presented via examples of application. This web based software has been designed and developed aiming to ensure insights over the huge amount of ISMR data that is fetched every day on an integrated platform. The software applies and adapts time series mining and information visualization techniques to extend the possibilities of exploring and analyzing ISMR data. The software is available to the scientific community through the World Wide Web, therefore constituting an analysis infrastructure that complements the monitoring one, providing support for researching ionospheric scintillation in the GNSS context. Interested researchers can access the functionalities without cost at http://is-cigala-calibra.fct.unesp.br/, under online request to the Space Geodesy Study Group from UNESP – Univ Estadual Paulista at Presidente Prudente.